2009
DOI: 10.3989/scimar.2009.73n2259
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sewage discharge on <em>Melarhaphe neritoides</em> (Gastropoda: Littorinidae) population dynamics

Abstract: SuMMarY: The discharges of sewage effluent treatment plants has a major impact on coastal communities. in our study area (western coast of Portugal) Melarhaphe neritoides (l. 1758) is the dominant high-shore gastropod. Two populations of M. neritoides were studied in order to understand the impact of sewage discharges on intertidal communities: one population in an impacted area and the other in a similar but unimpacted area (reference site). environmental data and abundance, biomass, population structure and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…However, to assess the effect of sewage discharges on the population of M. neritoides it is necessary to study the population along all tidal height, and not only in the littoral fringe. Planktonic larvae settle on the lower levels of rocky shores and then start moving upshore, resulting in a shell size gradient (Cabral-Oliveira et al, 2009). The results obtained in this work confirmed previous findings (Cabral-Oliveira et al, 2009) where the density of M. neritoides was higher in the impacted area as a result of massive settlement.…”
Section: Littoral Fringementioning
confidence: 99%
See 1 more Smart Citation
“…However, to assess the effect of sewage discharges on the population of M. neritoides it is necessary to study the population along all tidal height, and not only in the littoral fringe. Planktonic larvae settle on the lower levels of rocky shores and then start moving upshore, resulting in a shell size gradient (Cabral-Oliveira et al, 2009). The results obtained in this work confirmed previous findings (Cabral-Oliveira et al, 2009) where the density of M. neritoides was higher in the impacted area as a result of massive settlement.…”
Section: Littoral Fringementioning
confidence: 99%
“…Planktonic larvae settle on the lower levels of rocky shores and then start moving upshore, resulting in a shell size gradient (Cabral-Oliveira et al, 2009). The results obtained in this work confirmed previous findings (Cabral-Oliveira et al, 2009) where the density of M. neritoides was higher in the impacted area as a result of massive settlement. Also in this work was found a higher number of juveniles in the eulittoral near the outfall.…”
Section: Littoral Fringementioning
confidence: 99%
“…On both shores (Atlantic and Mediterranean), impacted locations were characterized by the presence of an outfall discharging effluents directly on the rocky shore in the intertidal zone. Previous studies have already reported the impact of sewage discharges on macrofauna, meiofauna and fish assemblages in these areas (Guidetti et al 2003;Terlizzi et al 2005b;Fraschetti et al 2006;Cabral-Oliveira et al 2009). Both outfalls release secondary treated effluents from a human population of 30,000 to 40,000.…”
Section: Study Areasmentioning
confidence: 99%